Cerai Gugat Akibat Murtad (Studi Putusan Pengadilan Agama Palu No: 0249/Pdt.G/2016/PA.Pal) - Aristanti, Diana; Susanti, Dyah Ochtorina; Andini , Pratiwi Pusphitho (University of Jember, 2017)
Marriage can be over when one of the parties becomes apostate in which apostate may cause problems of housewifery. In this research, it argues that the judge adopts a verdict according to the Law Number 1/ 1974 and Compilation of Islamic Law. The article uses legal research which accords to the norms in the positive law including the judge decision. It concludes that apostate can affects the marriage and the children right to inheritance. Additionally, divorce may not be renewed except both conducts a new marriage. In pertaining to the children right to heritance, children could not inherit their apostate parent(s) because Islamic law determines that apostate can be the reason of losing the right to inheritance. Keywords: Divorce, Apostate, Adjudication, Children Right to Inheritance.